Dry Reforming of Shale Gas and Carbon Dioxide with Ni‐Ce‐Al2O3 Catalyst: Syngas Production Enhanced over Ni‐CeOx Formation. Issue 20 (11th September 2018) - Liu, Yan; Wu, Ye; Akhtamberdinova, Zarina; Chen, Xiaoping; Jiang, Guodong; Liu, Dong
Abstract: The dry reforming of shale gas (methane and ethane with an average ratio of 4 : 1) with carbon dioxide (DRS) is considered to be a promising way to produce syngas, which widens the utilization of shale gas and mitigates carbon dioxide emission. In this paper, Ce modified Ni‐based catalysts were developed and the corresponding catalytic performances for DRS were investigated with a fixed bed reactor. Results showed that the catalyst containing 5 wt% of Ni and 5 wt% of Ce performed a best catalytic effect, including the selectivity of syngas and the carbon resistance performance, which is due to the good metal dispersion, strong interaction between Ni and Ce, and the formation of Ni‐CeOx solid solution. The electron transfer between Ni and Ce, substitution of Ni for Ce, and the sequential oxygen vacancies or defects, play significant roles in activating CH4, C2 H6 and CO2 . The conversion of reactant gas increased with temperature, while the selectivity of syngas is little affected with temperature. In addition, the desired catalyst containing 5 wt% of Ni and 5 wt% of Ce showed good stability in the long‐time operation, which indicates that the Ce modified Ni‐based catalyst is a promising one for the dry reforming of shale gas. Abstract : High fives ! The catalyst 5Ni‐5Ce exhibits the best catalytic performance in the dry reforming of shale gas and CO2 . The introduction of Ce creates strong interaction between Ni and Ce, which enhances the electron transfer between them. And the substitution of Ni for Ce produces oxygen vacancies and defects, which can accelerate the adsorption and activation of the reactant gases molecule, further promoting the reaction.